Saddle tilt during uphill cycling improves perceived comfort levels, with corresponding effects on saddle pressure in highly trained cyclists - Hynd, J.; Cooley, D.; Graham, M. (Journal of Science and Cycling, 2017)
Introduction Competitive cyclists often experience hand, foot, and saddle discomfort, creating potential for overuse injury and performance decrement (Bressel & Cronin, 2005, Journal of Biomechanics, 38, 1325-1331). The saddle is the most significant contact point, with uphill cycling (UC) performance being considered as the defining factor for success in the majority of cycling disciplines (Bertucci, Grappe, Girard, Betik, & Rouillon, 2005, Journal of Biomechanics, 38, 1003-1010). However, there is limited research related to bicycle saddle position, and in particular UC. (Caddy, Timmis & Gordon, 2016, Journal of Science in Cycling, 5, 18-25; Fonda & Sarabon, 2010, Sport Science Review, 19, 187-210).